2005
DOI: 10.1089/cbr.2005.20.16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Clinical Evaluation of125I-Radiolabeled Humanized CC49 Monoclonal Antibody (HuCC49ΔCH2) in Recurrent and Metastatic Colorectal Cancer Patients

Abstract: C(H)2 region deletion of HuCC49DeltaC(H)2 MAb did not alter the pharmacokinetics compared to murine CC49. The favorable partition coefficient K of HuCC49DeltaC(H)2 MAb into tumors supports its use in RIGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Compared with murine CC49 antibody, the humanized antibody will overcome immunogenicity problem in clinical investigation and the deletion of C H 2 domain will decrease the size of nanoconjugates. Our previous studies25, 36 showed that HuCC49ΔCH2 could specifically bind to LS174T colon cancer cells which had overexpression of TAG-72. The in vitro binding studies by fluorescence microscopy, Prussian blue staining and MRI scan showed the specific targeting of the HuCC49ΔCH2 labeled SPIOs (MAb-SPIOs) in LS174T colon cancer cells in comparison with SPIOs and IgG-SPIOs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with murine CC49 antibody, the humanized antibody will overcome immunogenicity problem in clinical investigation and the deletion of C H 2 domain will decrease the size of nanoconjugates. Our previous studies25, 36 showed that HuCC49ΔCH2 could specifically bind to LS174T colon cancer cells which had overexpression of TAG-72. The in vitro binding studies by fluorescence microscopy, Prussian blue staining and MRI scan showed the specific targeting of the HuCC49ΔCH2 labeled SPIOs (MAb-SPIOs) in LS174T colon cancer cells in comparison with SPIOs and IgG-SPIOs.…”
Section: Discussionmentioning
confidence: 99%
“…[106] For example, the murine anti-TAG-72 mAb (CC49) used in a phase I clinical trial for ovarian cancer induced human anti-mouse-antibody response [107]. However, another pilot clinical trial demonstrated that the humanized anti-TAG-72 antibody did not induce any immunogenic response, and the antibody is suitable for tumor targeting in human patients with high specificity and affinity [108]. Moreover, the same group demonstrated that this anti-TAG-72 humanized antibody (HuCC49ΔCH2) conjugated β-galactosidase selectively activated the geldanamycin prodrug (17-AG-C2_Gal).…”
Section: Enzyme Activated Prodrugmentioning
confidence: 99%
“…Anti-TAG-72 monoclonal antibodies have been studied in preclinical animal models as well as in humans for cancer detection based on their high specificity against cancer antigens in various solid cancers 2. As previously reported, we have utilized monoclonal antibodies against TAG-72 for tumor detection in radioimmunoguided surgery (RIGS) 37. Historically, RIGS combined radioactive-labeled (i.e., I 125 ) monoclonal antibodies and a handheld gamma probe for the intraoperative detection and resection of tumor-bearing tissues in colorectal cancer patients 5.…”
Section: Introductionmentioning
confidence: 99%